Waterproof anti-corrosion fireproof coating and preparation method thereof

By using organic-inorganic hybrid resins, microencapsulated ammonium polyphosphate, pentaerythritol/montmorillonite composites, nano ZnFe2O4 and calcium-ion modified silicon microspheres in fire-retardant coatings, a dense hydrophobic network and physical shielding mechanism are formed, which solves the problems of poor water resistance and insufficient anti-corrosion performance of existing fire-retardant coatings in humid environments, and achieves efficient fire and corrosion resistance.

CN119842318AActive Publication Date: 2025-04-18CHANGSHA MINDE FIRE ENG PAINT CO LTD

Patent Information

Application Number
CN202510319783.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The existing fire-resistant coatings have poor water resistance and insufficient corrosion resistance in humid environments, making it difficult to meet the needs of outdoor steel structures.

Method used

A water-resistant and anti-corrosion-resistant fire-resistant coating is used, and its composition includes organic-inorganic hybrid resin, microencapsulated ammonium polyphosphate, pentaerythritol/montmorillonite composite, nano ZnFe2O4 and calcium-ion modified silicon microspheres. Through the synergistic action of these components, a dense hydrophobic network, physical shielding and passivation mechanism is formed, which delays the decomposition rate and promotes the formation of the carbon layer.

Benefits of technology

It significantly improves the water resistance, corrosion resistance and fire resistance of the coating, ensuring the stability of the fire-proof layer and the structural strength of the metal substrate in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842318A_ABST
    Figure CN119842318A_ABST
Patent Text Reader

Abstract

The invention relates to a water-resistant anticorrosive fireproof coating and a preparation method thereof. The water-resistant anticorrosive fireproof coating is prepared from the following components in parts by weight: 60 to 80 parts of organic-inorganic hybrid resin, 20 to 30 parts of microencapsulated ammonium polyphosphate, 10 to 15 parts of pentaerythritol / montmorillonite compound, 6 to 9 parts of nano ZnFe2O4, 3 to 7 parts of calcium ion modified silicon microspheres, 0.3 to 0.6 part of wetting agent and 3 to 5 parts of propyl alcohol. A hydrophobic network is constructed through an organic-inorganic hybrid base material, nano zinc ferrite and calcium ion modified silicon microspheres are used for synergic corrosion prevention, and a microencapsulation technology is used for cooperating with a pentaerythritol / montmorillonite compound to regulate and control decomposition kinetics of the flame retardant. The product is free of rusty spots after being soaked in high-temperature saline water for 20 days, the water contact angle is larger than or equal to 86 degrees, the fire-resistant temperature is improved compared with that of commercially available products, and the product is suitable for severe environments such as ships and offshore platforms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fire retardant coatings, and in particular to a water-resistant and anti-corrosion fire retardant coating and a preparation method thereof. Background Art

[0002] At present, steel structure buildings are widely used due to their advantages such as stable structure, large space, and convenient construction and recycling. However, steel structures are prone to lose stability in high temperature environments and are easily corroded in humid environments. Therefore, a coating with both fireproof and anti-corrosion functions is needed. Conventional resin base materials (such as ordinary acrylic acid) have high water absorption and are prone to swelling and peeling in humid environments, resulting in failure of the fireproof layer; some lack long-term anti-rust components, and the metal substrate is prone to electrochemical corrosion in high temperature and high humidity environments, reducing structural strength; and the addition of preservatives may destroy the structure of the expanded carbon layer, resulting in a decrease in fireproof efficiency. Therefore, existing fire retardant coatings often have problems such as poor water resistance and insufficient anti-corrosion performance, which are difficult to meet the use requirements of outdoor steel structures. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a water-resistant and anti-corrosion fire-retardant coating and a preparation method thereof, so as to solve the problem of mutual restriction of functional components of current fire-retardant coatings.

[0004] Technical solution: A water-resistant, anti-corrosion and fire-retardant coating, characterized in that it contains the following components and proportions by weight: 60-80 parts of organic-inorganic hybrid resin, 20-30 parts of microencapsulated ammonium polyphosphate, 10-15 parts of pentaerythritol / montmorillonite composite, 6-9 parts of nano ZnFe2O4, 3-7 parts of calcium ion modified silicon microspheres, 0.3-0.6 parts of wetting agent, and 3-5 parts of propanol.

[0005] Preferably, the method for preparing the organic-inorganic hybrid resin is as follows: adding terminal hydrogen silicone oil (2H2000) to a reaction bottle, adding p-hydroxyanisole with a weight of 0.05 times the weight of the terminal hydrogen silicone oil and a 1% chloroplatinic acid tetrahydrofuran solution with a volume of 1 times the weight of the terminal hydrogen silicone oil under stirring, adding 4-vinylbenzyl glycidyl ether with a weight of 0.2 times the weight of the terminal hydrogen silicone oil, heating and refluxing for 8 hours, reducing pressure to 80°C and concentrating until no liquid drips out to obtain a polysiloxane epoxy resin, and compounding the polysiloxane epoxy resin with silica sol (SiO2 particle size 20-40nm) at a volume ratio of 3:1-5:1 and stirring and mixing for 30 minutes to obtain the obtained product; the infrared spectrum of the prepared polysiloxane epoxy resin is shown in the attached Figure 1 , 1 H-NMR spectrum is attached Figure 2 , the infrared spectrum after solidification is attached Figure 3 .

[0006] Preferably, the preparation method of the calcium ion modified silicon microspheres is as follows: prepare a potassium hydroxide aqueous solution with a mass fraction of 12%, add an OP-10 emulsifier with a weight of 0.005 times the weight of the potassium hydroxide aqueous solution, slowly add vinyl trimethoxy silane with a weight of 0.2 times the weight of the potassium hydroxide solution under stirring, heat to 45°C and stir for 2h, add acetic acid aqueous solution with a volume fraction of 10% to adjust the pH to 5, filter, rinse with ethanol with a volume of 3 times the weight of the vinyl trimethyl silane, and vacuum dry at 100°C to constant weight to obtain silicon microspheres; add the obtained silicon microspheres to ethanol with a volume of 8 times the weight of the silicon microspheres, and ultrasonically 30min, add benzoin dimethyl ether whose weight is 0.05 times of the weight of silicon microspheres, stir and dissolve, add thioglycolic acid whose weight is 0.3 times of the weight of silicon microspheres, stir for 15min under ultraviolet irradiation, filter, rinse with ethanol, and dry in vacuum at 100℃ to constant weight to obtain thiol-modified silicon microspheres; add the obtained thiol-modified silicon microspheres to a 10% calcium chloride aqueous solution whose volume is 5 times of the weight of thiol-modified silicon microspheres, ultrasonicate for 30min, stir at room temperature for 12h, wash with water, wash with ethanol, and dry in vacuum at 100℃ to constant weight to obtain; the SEM picture of the prepared calcium ion-modified silicon microspheres is shown in the attached Figure 4 , infrared spectrum is attached Figure 5 .

[0007] Preferably, the preparation method of the microencapsulated ammonium polyphosphate is as follows: under argon protection, add ammonium polyphosphate to a reaction bottle, add ethyl acetate with a volume of 10 times the weight of ammonium polyphosphate, add 4,4'-diphenylmethane diisocyanate with a weight of 0.5 times the weight of ammonium polyphosphate and melamine with a weight of 0.3 times the weight of ammonium polyphosphate under stirring, heat to 55°C for reaction for 6h, add pentaerythritol with a weight of 0.4 times the weight of ammonium polyphosphate, reflux for reaction for 3h, add polyethylene glycol with a weight of 1 times the weight of ammonium polyphosphate, alkylphenol polyoxyethylene ether with a weight of 0.1 times the weight of ammonium polyphosphate and dibutyltin dilaurate with a weight of 0.05 times the weight of ammonium polyphosphate, continue reflux reaction for 2h, cool the reaction solution to room temperature and filter, wash the filter cake once with deionized water with a volume of 3 times the weight of ammonium polyphosphate, and dry it at 70°C in vacuum to constant weight; SEM images of the prepared microencapsulated ammonium polyphosphate and ammonium polyphosphate at different magnifications are shown in the attached Figure 6 .

[0008] Preferably, the preparation method of the pentaerythritol / montmorillonite composite is as follows: add pentaerythritol with a weight of 0.5 times the weight of montmorillonite to purified water with a volume of 10 times the weight of montmorillonite, heat to 60°C and stir for 20 minutes, add montmorillonite, stir for 15 minutes, adjust the pH to 3-4 with 2M hydrochloric acid aqueous solution, heat to 75°C and stir to react for 8 hours, filter, and wash with ethanol with a volume of 3 times the weight of montmorillonite for 10 minutes each time, wash three times, vacuum dry at 60°C to constant weight, and grind through a 200-mesh sieve to obtain.

[0009] Preferably, the preparation method of the nano ZnFe2O4 is as follows: according to the molar ratio of ferric nitrate nonahydrate: zinc nitrate hexahydrate = 2:1, the two are weighed and added to a reaction bottle, water with a volume 10 times the weight of the mixture of the two is added, stirred to dissolve, heated to 70°C for reaction for 1h, polysorbate with a weight of 0.2 times the weight of ferric nitrate nonahydrate is added under stirring, stirred for 30min, 10% citric acid aqueous solution is added dropwise to adjust the pH to 6, heated to 80°C for reaction for 2h, filtered, vacuum dried at 70°C to constant weight, and a precursor is obtained, the precursor is calcined at 500°C for 2h, and ground to obtain; the infrared spectrum of the prepared nano zinc ferrite crystal is shown in the attached Figure 7 The XRD diffraction patterns of nano zinc ferrite obtained after calcination at different temperatures for 2 h are shown in the attached Figure 8 The XRD patterns of the nano zinc ferrite crystal surface obtained after calcination at different temperatures for 2 h are shown in the attached Fig. 9 , the particle size analysis diagram of nano zinc ferrite is attached Fig.10 .

[0010] Preferably, the wetting agent is BYK-364.

[0011] A method for preparing a water-resistant and anti-corrosion fire-retardant coating comprises the following steps: S1. Add nano ZnFe2O4 and silicon microspheres into a sand mill and disperse at 2000 rpm until the fineness is ≤30 μm; S2, adding organic-inorganic hybrid resin, propanol, and wetting agent, stirring at 800 rpm for 20 min; S3, slowly add microencapsulated ammonium polyphosphate and pentaerythritol / montmorillonite composite, and treat with ultrasound (40kHz) at 40°C for 30min; S4, stirring and ripening for 24 hours before discharging.

[0012] Beneficial effects:

[0013] 1. Compound epoxy-modified silicone resin with silica sol to form a dense hydrophobic network. The epoxy group improves adhesion, the silicone chain segment reduces surface energy, and nano-SiO2 fills micropores to avoid the problem of fireproof layer failure caused by swelling and peeling of the coating in a humid environment.

[0014] 2. Nano zinc ferrite (ZnFe2O4) and ion exchange rust inhibitor (calcium ion modified silicon microspheres) work together to slow down the electrochemical corrosion of metal substrates in high temperature and high humidity environments through the dual mechanisms of physical shielding and passivation, maintain the structural strength of the metal substrate, and achieve long-term rust and corrosion prevention.

[0015] 3. Microencapsulated ammonium polyphosphate is combined with pentaerythritol / montmorillonite complex to slow down the decomposition rate and match the kinetics of carbon layer formation. Microencapsulated ammonium polyphosphate releases flame-retardant gases such as phosphoric acid and ammonia after thermal decomposition and forms a carbon layer. The pentaerythritol / montmorillonite complex can capture the decomposition products, promote the formation of a dense carbon layer, and inhibit the release of smoke. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The infrared spectrum of the polysiloxane epoxy resin synthesized by the present invention.

[0017] Figure 2 The polysiloxane epoxy resin synthesized by the present invention 1 H-NMR spectrum.

[0018] Figure 3 This is the infrared spectrum of the polysiloxane epoxy resin synthesized by the present invention after solidification.

[0019] Figure 4 This is a SEM image of the calcium ion-modified silicon microspheres of the present invention.

[0020] Figure 5 This is the infrared spectrum of the calcium ion modified silicon microspheres of the present invention.

[0021] Figure 6 The SEM images of the ammonium polyphosphate of the present invention and the microencapsulated ammonium polyphosphate at different magnifications; Among them, a is ammonium polyphosphate magnified 2000 times, b is ammonium polyphosphate magnified 5000 times, c is microencapsulated ammonium polyphosphate magnified 2000 times, and d is microencapsulated ammonium polyphosphate magnified 5000 times.

[0022] Figure 7 The infrared spectrum of the nano zinc ferrite crystal of the present invention is shown in FIG.

[0023] Figure 8 The XRD diffraction patterns of nano zinc ferrite obtained after calcination for 2 hours at different temperatures in the present invention; Among them, a is the XRD diffraction pattern of nano zinc ferrite obtained after calcination at 300°C for 2h, b is the XRD diffraction pattern of nano zinc ferrite obtained after calcination at 400°C for 2h, c is the XRD diffraction pattern of nano zinc ferrite obtained after calcination at 500°C for 2h, and d is the XRD diffraction pattern of nano zinc ferrite obtained after calcination at 600°C for 2h.

[0024] Fig. 9 The XRD patterns of the nano zinc ferrite crystal surface obtained after calcination for 2 hours at different temperatures in the present invention; Among them, a is the XRD spectrum of the nano-zinc ferrite crystal surface obtained after calcination at 300°C for 2h, b is the XRD spectrum of the nano-zinc ferrite crystal surface obtained after calcination at 400°C for 2h, c is the XRD spectrum of the nano-zinc ferrite crystal surface obtained after calcination at 500°C for 2h, and d is the XRD spectrum of the nano-zinc ferrite crystal surface obtained after calcination at 600°C for 2h.

[0025] Fig.10 This is a particle size analysis diagram of the nano zinc ferrite obtained in the present invention. DETAILED DESCRIPTION

[0026] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0027] Embodiment 1

[0028] Raw materials preparation: Organic-inorganic hybrid resin: Add hydrogen-terminated silicone oil (2H2000) to a reaction bottle, add p-hydroxyanisole in an amount 0.05 times the weight of the hydrogen-terminated silicone oil and a 1% chloroplatinic acid tetrahydrofuran solution in an amount 1 times the weight of the hydrogen-terminated silicone oil under stirring, add 4-vinylbenzyl glycidyl ether in an amount 0.2 times the weight of the hydrogen-terminated silicone oil, heat under reflux for 8 hours, and concentrate at 80°C under reduced pressure until no liquid drips out to obtain a polysilicone epoxy resin. Compound the polysilicone epoxy resin with silica sol (SiO2 particle size 20-40nm) at a volume ratio of 3:1-5:1 and stir and mix for 30 minutes to obtain the resin.

[0029] Calcium ion modified silica microspheres: prepare a potassium hydroxide aqueous solution with a mass fraction of 12%, add an OP-10 emulsifier with a weight of 0.005 times the weight of the potassium hydroxide aqueous solution, slowly add vinyl trimethoxy silane with a weight of 0.2 times the weight of the potassium hydroxide solution under stirring, heat to 45°C and stir for 2h, add a 10% acetic acid aqueous solution with a volume fraction to adjust the pH to 5, filter, rinse with ethanol with a volume of 3 times the weight of vinyl trimethyl silane, and vacuum dry at 100°C to constant weight to obtain silica microspheres; add ethanol with a volume of 8 times the weight of the silica microspheres to the obtained silica microspheres. The obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and the mixture was ultrasonicated for 30 minutes, and benzoin dimethyl ether with a weight of 0.05 times the weight of the silicon microspheres was added, and after stirring and dissolving, thioglycolic acid with a weight of 0.3 times the weight of the silicon microspheres was added, and stirred for 15 minutes under ultraviolet irradiation, filtered, rinsed with ethanol, and dried at 100°C in vacuum to constant weight to obtain thiol-modified silicon microspheres; the obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and ultrasonicated for 30 minutes, and stirred at room temperature for 12 hours, washed with water, washed with ethanol, and dried at 100°C in vacuum to constant weight.

[0030] Microencapsulated ammonium polyphosphate: under argon protection, add ammonium polyphosphate into the reaction bottle, add ethyl acetate with a volume of 10 times the weight of ammonium polyphosphate, add 4,4'-diphenylmethane diisocyanate with a weight of 0.5 times the weight of ammonium polyphosphate and melamine with a weight of 0.3 times the weight of ammonium polyphosphate under stirring, heat to 55°C for reaction for 6h, add pentaerythritol with a weight of 0.4 times the weight of ammonium polyphosphate, reflux for reaction for 3h, add polyethylene glycol with a weight of 1 times the weight of ammonium polyphosphate, alkylphenol polyoxyethylene ether with a weight of 0.1 times the weight of ammonium polyphosphate and dibutyltin dilaurate with a weight of 0.05 times the weight of ammonium polyphosphate, continue reflux reaction for 2h, cool the reaction solution to room temperature and filter, wash the filter cake once with deionized water with a volume of 3 times the weight of ammonium polyphosphate, and dry it at 70°C in vacuum until constant weight is obtained.

[0031] Pentaerythritol / montmorillonite composite: Add pentaerythritol with a weight of 0.5 times the weight of montmorillonite to purified water with a volume of 10 times the weight of montmorillonite, heat to 60°C and stir for 20 minutes, add montmorillonite, stir for 15 minutes, adjust the pH to 3-4 with 2M hydrochloric acid aqueous solution, heat to 75°C and stir to react for 8 hours, filter, and wash with ethanol with a volume of 3 times the weight of montmorillonite for 10 minutes each time, wash three times, vacuum dry at 60°C to constant weight, and grind through a 200-mesh sieve.

[0032] Nano ZnFe2O4: Weigh ferric nitrate nonahydrate and zinc nitrate hexahydrate in a molar ratio of 2:1 and add them to a reaction bottle, add water 10 times the weight of the mixture, stir to dissolve, heat to 70°C to react for 1 hour, add polysorbate 0.2 times the weight of ferric nitrate nonahydrate with stirring, stir for 30 minutes, add 10% citric acid aqueous solution to adjust the pH to 6, heat to 80°C to react for 2 hours, filter, and dry at 70°C in vacuum to constant weight to obtain a precursor, calcine the precursor at 500°C for 2 hours, and grind to obtain the precursor.

[0033] Preparation process: S1, add 30g nano ZnFe2O4 and 15g calcium ion modified silicon microspheres into a sand mill, and disperse at 2000rpm until the fineness is ≤30μm; S2, add 300g organic-inorganic hybrid resin, 15g propanol, 1.5g wetting agent BYK-364, and stir at 800rpm for 20min; S3, slowly add 100g of microencapsulated ammonium polyphosphate and 50g of pentaerythritol / montmorillonite composite, and perform ultrasonic treatment (40kHz) at 40℃ for 30min; S4, stirring and ripening for 24 hours before discharging.

[0034] Embodiment 2

[0035] Raw materials preparation: Organic-inorganic hybrid resin: Add hydrogen-terminated silicone oil (2H2000) to a reaction bottle, add p-hydroxyanisole in an amount 0.05 times the weight of the hydrogen-terminated silicone oil and a 1% chloroplatinic acid tetrahydrofuran solution in an amount 1 times the weight of the hydrogen-terminated silicone oil under stirring, add 4-vinylbenzyl glycidyl ether in an amount 0.2 times the weight of the hydrogen-terminated silicone oil, heat under reflux for 8 hours, and concentrate at 80°C under reduced pressure until no liquid drips out to obtain a polysilicone epoxy resin. Compound the polysilicone epoxy resin with silica sol (SiO2 particle size 20-40nm) at a volume ratio of 3:1-5:1 and stir and mix for 30 minutes to obtain the resin.

[0036] Calcium ion modified silica microspheres: prepare a potassium hydroxide aqueous solution with a mass fraction of 12%, add an OP-10 emulsifier with a weight of 0.005 times the weight of the potassium hydroxide aqueous solution, slowly add vinyl trimethoxy silane with a weight of 0.2 times the weight of the potassium hydroxide solution under stirring, heat to 45°C and stir for 2h, add a 10% acetic acid aqueous solution with a volume fraction to adjust the pH to 5, filter, rinse with ethanol with a volume of 3 times the weight of vinyl trimethyl silane, and vacuum dry at 100°C to constant weight to obtain silica microspheres; add ethanol with a volume of 8 times the weight of the silica microspheres to the obtained silica microspheres. The obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and the mixture was ultrasonicated for 30 minutes, and benzoin dimethyl ether with a weight of 0.05 times the weight of the silicon microspheres was added, and after stirring and dissolving, thioglycolic acid with a weight of 0.3 times the weight of the silicon microspheres was added, and stirred for 15 minutes under ultraviolet irradiation, filtered, rinsed with ethanol, and dried at 100°C in vacuum to constant weight to obtain thiol-modified silicon microspheres; the obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and ultrasonicated for 30 minutes, and stirred at room temperature for 12 hours, washed with water, washed with ethanol, and dried at 100°C in vacuum to constant weight.

[0037] Microencapsulated ammonium polyphosphate: under argon protection, add ammonium polyphosphate into the reaction bottle, add ethyl acetate with a volume of 10 times the weight of ammonium polyphosphate, add 4,4'-diphenylmethane diisocyanate with a weight of 0.5 times the weight of ammonium polyphosphate and melamine with a weight of 0.3 times the weight of ammonium polyphosphate under stirring, heat to 55°C for reaction for 6h, add pentaerythritol with a weight of 0.4 times the weight of ammonium polyphosphate, reflux for reaction for 3h, add polyethylene glycol with a weight of 1 times the weight of ammonium polyphosphate, alkylphenol polyoxyethylene ether with a weight of 0.1 times the weight of ammonium polyphosphate and dibutyltin dilaurate with a weight of 0.05 times the weight of ammonium polyphosphate, continue reflux reaction for 2h, cool the reaction solution to room temperature and filter, wash the filter cake once with deionized water with a volume of 3 times the weight of ammonium polyphosphate, and dry it at 70°C in vacuum until constant weight is obtained.

[0038] Pentaerythritol / montmorillonite composite: Add pentaerythritol with a weight of 0.5 times the weight of montmorillonite to purified water with a volume of 10 times the weight of montmorillonite, heat to 60°C and stir for 20 minutes, add montmorillonite, stir for 15 minutes, adjust the pH to 3-4 with 2M hydrochloric acid aqueous solution, heat to 75°C and stir to react for 8 hours, filter, and wash with ethanol with a volume of 3 times the weight of montmorillonite for 10 minutes each time, wash three times, vacuum dry at 60°C to constant weight, and grind through a 200-mesh sieve.

[0039] Nano ZnFe2O4: Weigh ferric nitrate nonahydrate and zinc nitrate hexahydrate in a molar ratio of 2:1 and add them to a reaction bottle, add water 10 times the weight of the mixture, stir to dissolve, heat to 70°C to react for 1 hour, add polysorbate 0.2 times the weight of ferric nitrate nonahydrate with stirring, stir for 30 minutes, add 10% citric acid aqueous solution to adjust the pH to 6, heat to 80°C to react for 2 hours, filter, and dry at 70°C in vacuum to constant weight to obtain a precursor, calcine the precursor at 500°C for 2 hours, and grind to obtain the precursor.

[0040] Preparation process: S1, add 37.5g nano ZnFe2O4 and 25g calcium ion modified silicon microspheres into a sand mill, and disperse at 2000rpm to a fineness of ≤30μm; S2, add 350g organic-inorganic hybrid resin, 20g propanol, 2g wetting agent BYK-364, and stir at 800rpm for 20min; S3, slowly add 125g of microencapsulated ammonium polyphosphate and 60g of pentaerythritol / montmorillonite composite, and treat with ultrasound (40kHz) at 40℃ for 30min; S4, stirring and ripening for 24 hours before discharging.

[0041] Embodiment 3

[0042] Raw materials preparation: Organic-inorganic hybrid resin: Add hydrogen-terminated silicone oil (2H2000) to a reaction bottle, add p-hydroxyanisole in an amount 0.05 times the weight of the hydrogen-terminated silicone oil and a 1% chloroplatinic acid tetrahydrofuran solution in an amount 1 times the weight of the hydrogen-terminated silicone oil under stirring, add 4-vinylbenzyl glycidyl ether in an amount 0.2 times the weight of the hydrogen-terminated silicone oil, heat under reflux for 8 hours, and concentrate at 80°C under reduced pressure until no liquid drips out to obtain a polysilicone epoxy resin. Compound the polysilicone epoxy resin with silica sol (SiO2 particle size 20-40nm) at a volume ratio of 3:1-5:1 and stir and mix for 30 minutes to obtain the resin.

[0043] Calcium ion modified silica microspheres: prepare a potassium hydroxide aqueous solution with a mass fraction of 12%, add an OP-10 emulsifier with a weight of 0.005 times the weight of the potassium hydroxide aqueous solution, slowly add vinyl trimethoxy silane with a weight of 0.2 times the weight of the potassium hydroxide solution under stirring, heat to 45°C and stir for 2h, add a 10% acetic acid aqueous solution with a volume fraction to adjust the pH to 5, filter, rinse with ethanol with a volume of 3 times the weight of vinyl trimethyl silane, and vacuum dry at 100°C to constant weight to obtain silica microspheres; add ethanol with a volume of 8 times the weight of the silica microspheres to the obtained silica microspheres. The obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and the mixture was ultrasonicated for 30 minutes, and benzoin dimethyl ether with a weight of 0.05 times the weight of the silicon microspheres was added, and after stirring and dissolving, thioglycolic acid with a weight of 0.3 times the weight of the silicon microspheres was added, and stirred for 15 minutes under ultraviolet irradiation, filtered, rinsed with ethanol, and dried at 100°C in vacuum to constant weight to obtain thiol-modified silicon microspheres; the obtained thiol-modified silicon microspheres were added into a 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, and ultrasonicated for 30 minutes, and stirred at room temperature for 12 hours, washed with water, washed with ethanol, and dried at 100°C in vacuum to constant weight.

[0044] Microencapsulated ammonium polyphosphate: under argon protection, add ammonium polyphosphate into the reaction bottle, add ethyl acetate with a volume of 10 times the weight of ammonium polyphosphate, add 4,4'-diphenylmethane diisocyanate with a weight of 0.5 times the weight of ammonium polyphosphate and melamine with a weight of 0.3 times the weight of ammonium polyphosphate under stirring, heat to 55°C for reaction for 6h, add pentaerythritol with a weight of 0.4 times the weight of ammonium polyphosphate, reflux for reaction for 3h, add polyethylene glycol with a weight of 1 times the weight of ammonium polyphosphate, alkylphenol polyoxyethylene ether with a weight of 0.1 times the weight of ammonium polyphosphate and dibutyltin dilaurate with a weight of 0.05 times the weight of ammonium polyphosphate, continue reflux reaction for 2h, cool the reaction solution to room temperature and filter, wash the filter cake once with deionized water with a volume of 3 times the weight of ammonium polyphosphate, and dry it at 70°C in vacuum until constant weight is obtained.

[0045] Pentaerythritol / montmorillonite composite: Add pentaerythritol with a weight of 0.5 times the weight of montmorillonite to purified water with a volume of 10 times the weight of montmorillonite, heat to 60°C and stir for 20 minutes, add montmorillonite, stir for 15 minutes, adjust the pH to 3-4 with 2M hydrochloric acid aqueous solution, heat to 75°C and stir to react for 8 hours, filter, and wash with ethanol with a volume of 3 times the weight of montmorillonite for 10 minutes each time, wash three times, vacuum dry at 60°C to constant weight, and grind through a 200-mesh sieve.

[0046] Nano ZnFe2O4: Weigh ferric nitrate nonahydrate and zinc nitrate hexahydrate in a molar ratio of 2:1 and add them to a reaction bottle, add water 10 times the weight of the mixture, stir to dissolve, heat to 70°C to react for 1 hour, add polysorbate 0.2 times the weight of ferric nitrate nonahydrate with stirring, stir for 30 minutes, add 10% citric acid aqueous solution to adjust the pH to 6, heat to 80°C to react for 2 hours, filter, and dry at 70°C in vacuum to constant weight to obtain a precursor, calcine the precursor at 500°C for 2 hours, and grind to obtain the precursor.

[0047] Preparation process: S1, add 45g nano ZnFe2O4 and 35g calcium ion modified silicon microspheres into a sand mill, and disperse at 2000rpm to a fineness of ≤30μm; S2, add 400g organic-inorganic hybrid resin, 25g propanol, 3g wetting agent BYK-364, and stir at 800rpm for 20min; S3, slowly add 150g of microencapsulated ammonium polyphosphate and 75g of pentaerythritol / montmorillonite composite, and treat with ultrasound (40kHz) at 40℃ for 30min; S4, stirring and ripening for 24 hours before discharging.

[0048] The water-resistant, anti-corrosion and fire-retardant coatings prepared in Examples 1 to 3 were compared with commercially available intumescent fire-retardant coatings, and their water resistance was measured by a water contact angle test using a static contact angle method. Their fire retardant properties were measured by testing their initial decomposition temperature (temperature at which weight loss was 10%) and half-life temperature (temperature at which weight loss was 50%) using a thermal gravimetric method. The coatings were applied to iron rods, and after complete curing, the rods were immersed in a 3% sodium chloride aqueous solution at 95°C for 20 days to observe their anti-corrosion properties.

[0049] Table 1 Test results of the embodiments and commercially available fire retardant coatings

[0050] By comparing the embodiments with commercially available intumescent fire retardant coatings, the contact angle with water is ≥86°, which is far better than the commercially available 57.6°. The initial decomposition temperature and the half-life temperature are both higher than the commercially available products. After being soaked in high-temperature salt water, the effect is also better than the commercially available products. By comparing the data and phenomena, it can be seen that the water resistance, corrosion resistance and fire resistance of the present invention are significantly improved compared with the commercially available products.

[0051] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A water-resistant and anti-corrosion fire-retardant coating, characterized in that: The composition comprises the following components and their proportions by weight: 60-80 parts of organic-inorganic hybrid resin, 20-30 parts of microencapsulated ammonium polyphosphate, 10-15 parts of pentaerythritol / montmorillonite composite, 6-9 parts of nano ZnFe2O4, 3-7 parts of calcium ion modified silicon microspheres, 0.3-0.6 parts of wetting agent, and 3-5 parts of propanol; The preparation method of the organic-inorganic hybrid resin is as follows: add hydrogen-terminated silicone oil into a reaction bottle, add p-hydroxyanisole whose weight is 0.05 times of the weight of the hydrogen-terminated silicone oil and a 1% chloroplatinic acid tetrahydrofuran solution whose volume is 1 times of the weight of the hydrogen-terminated silicone oil under stirring, add 4-vinylbenzyl glycidyl ether whose weight is 0.2 times of the weight of the hydrogen-terminated silicone oil, heat and reflux for reaction for 8 hours, reduce pressure to 80°C and concentrate until no liquid drips out to obtain a polysilicone epoxy resin, and compound the polysilicone epoxy resin with silica sol at a volume ratio of 3:1-5:1 and stir and mix for 30 minutes to obtain the obtained resin.

2. The water-resistant and anti-corrosion fire-retardant coating according to claim 1, characterized in that: The preparation method of calcium ion modified silicon microspheres is as follows: prepare a potassium hydroxide aqueous solution with a mass fraction of 12%, add an OP-10 emulsifier with a weight of 0.005 times the weight of the potassium hydroxide aqueous solution, slowly add vinyltrimethoxysilane with a weight of 0.2 times the weight of the potassium hydroxide solution under stirring, heat to 45°C and stir for 2h, add acetic acid aqueous solution with a volume fraction of 10% to adjust the pH to 5, filter, rinse with ethanol with a volume of 3 times the weight of vinyltrimethylsilane, and vacuum dry at 100°C to constant weight to obtain silicon microspheres; add ethanol with a volume of 8 times the weight of the silicon microspheres to the obtained silicon microspheres. The obtained thiol-modified silicon microspheres were prepared by adding 10% calcium chloride aqueous solution with a volume of 5 times the weight of the thiol-modified silicon microspheres, ultrasonicating for 30 minutes, stirring at room temperature for 12 hours, washing with water, washing with ethanol, and drying at 100°C in vacuum to constant weight.

3. The water-resistant and anti-corrosion fire-retardant coating according to claim 1, characterized in that: The preparation method of microencapsulated ammonium polyphosphate is as follows: under argon protection, ammonium polyphosphate is added to a reaction bottle, ethyl acetate is added in a volume 10 times the weight of the ammonium polyphosphate, 4,4'-diphenylmethane diisocyanate in a volume 0.5 times the weight of the ammonium polyphosphate and melamine in a volume 0.3 times the weight of the ammonium polyphosphate are added under stirring, the reaction is heated to 55°C for 6 hours, pentaerythritol in a volume 0.4 times the weight of the ammonium polyphosphate is added, the reaction is refluxed for 3 hours, polyethylene glycol in a volume 1 times the weight of the ammonium polyphosphate, alkylphenol polyoxyethylene ether in a volume 0.1 times the weight of the ammonium polyphosphate and dibutyltin dilaurate in a volume 0.05 times the weight of the ammonium polyphosphate are added, the reaction is continued under reflux for 2 hours, the reaction solution is cooled to room temperature and filtered, the filter cake is slurried and washed once with deionized water in a volume 3 times the weight of the ammonium polyphosphate, and vacuum dried at 70°C to constant weight.

4. The water-resistant and anti-corrosion fire-retardant coating according to claim 1, characterized in that: The preparation method of the pentaerythritol / montmorillonite composite is as follows: add pentaerythritol with a weight of 0.5 times the weight of montmorillonite to purified water with a volume of 10 times the weight of montmorillonite, heat to 60°C and stir for 20 minutes, add montmorillonite, stir for 15 minutes, adjust the pH to 3-4 with 2M hydrochloric acid aqueous solution, heat to 75°C and stir to react for 8 hours, filter, and wash with ethanol with a volume of 3 times the weight of montmorillonite for 10 minutes each time, wash three times, vacuum dry at 60°C to constant weight, and grind through a 200-mesh sieve to obtain.

5. The water-resistant and anti-corrosion fire-retardant coating according to claim 1, characterized in that: The preparation method of nano ZnFe2O4 is as follows: weigh ferric nitrate nonahydrate and zinc nitrate hexahydrate in a molar ratio of 2:1 and add them to a reaction bottle, add water 10 times the weight of the mixture of the two, stir to dissolve, heat to 70°C to react for 1 hour, add polysorbate 0.2 times the weight of ferric nitrate nonahydrate under stirring, stir for 30 minutes, add 10% citric acid aqueous solution to adjust the pH to 6, heat to 80°C to react for 2 hours, filter, and dry at 70 degrees Celsius in vacuum to constant weight to obtain a precursor, calcine the precursor at 500°C for 2 hours, and grind it.

6. The water-resistant and anticorrosive fire-retardant coating according to claim 1, characterized in that: The wetting agent is BYK-364.

7. A method for preparing a water-resistant and anticorrosive fire-retardant coating according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1. Add nano ZnFe2O4 and silicon microspheres into a sand mill and disperse at 2000 rpm until the fineness is ≤30 μm; S2, adding organic-inorganic hybrid resin, propanol, and wetting agent, stirring at 800 rpm for 20 min; S3, slowly add microencapsulated ammonium polyphosphate and pentaerythritol / montmorillonite composite, and perform ultrasonic treatment at 40°C for 30 min; S4, stirring and ripening for 24 hours before discharging.

Citation Information

Patent Citations

  • Polyurethane microcapsulated inorganic phosphonium flame retardant and preparation thereof

    CN101376811A

  • Nano-sphere with elements of silicon, cobalt and like as well as synergetic ammonium polyphosphate flame resistant polypropylene material thereof

    CN104744811A

  • Preparation method of phosphorus-nitrogen-silicon synergistic phyllosilicate flame retardant

    CN104774344A

  • Production method for cation ultraviolet light curing frame glue used for organic electroluminescence displayer

    CN104946186A

  • Preparation method of zinc ferrite / tin dioxide composite nano material with good gas-sensitive response to acetone gas

    CN110240205A

Cited By

  • Corrosion-resistant environment-friendly coating as well as preparation method and application thereof

    CN120383864A

  • Thermoplastic polyarylene sulfide-based composite cable and preparation method thereof

    CN120441983A